PENGEMBANGAN MEDIA PEMBELAJARAN JARINGAN KOMPUTER BERBASIS ANDROID DENGAN MIT APP INVENTOR KELAS X SEMESTER GANJIL DI SMA N 1 AMBARAWA - Andriyani, Fitri Andriyani; Supandi, Supandi; Wijonarko, Wijonarko (Universitas PGRI Semarang, 2021)
This research is based on the computer network learning process carried out by the teacher and students delivering material that is done in conventional ways such as lectures and books make students less active so that it results in lower student grades not good. To overcome this problem, a media was developed learning to use Android is more effective, efficient, and can improve enthusiasm and student learning outcomes. This research was conducted to describe the process of development of learning media and measuring the level of effectiveness and feasibility learning media for computer network class x odd semester at SMA N 1 Ambarawa. The purpose of the research is to increase students' interest in learning by using information and communication technology, especially Smartphones in the form of applications android. This study uses themethod Research and Development with the model development waterfall which has several stages of requirements analysis, system design, implementation, system testing and maintenance. This product design includes data, navigation, flowchart and user interface. With data collection techniques carried out by means of observation, interviews and questionnaires. The results showed that material expert validation got a score of 96%, while for validation by media experts get 89% so it can be concluded that the development of learning media is very valid with very good criteria for used. Percentage of respondents by students with practicality test average results a percentage of 85.5% can be concluded that the development of learning media Android-based is very practical with very good criteria for use.Suggestions that can be given should be from SMA N 1 Ambarawa to get apply learning media using android to students as one of the supporters of the learning process.